Using Psychodynamic Approaches with Voluntarily Childless Couples: A Literature Review - Hillier, Kaitlyn (Canadian Journal of Counselling and Psychotherapy, 2017)
Culturally sensitive psychodynamic and psychoanalytic concepts and methods are an effective means to address the unique needs of voluntarily childless (VC) couples. The discussion will describe voluntary childlessness and outline the issues of marginalization faced by this growing demographic of individuals and couples, based on a comprehensive literature review. Additionally, the discussion will outline how the inclusion of psychodynamic/ psychoanalytic couple therapies, such as object relations couple therapy, will facilitate culturally sensitive therapeutic practices. Lastly, this article will describe and suggest measures that could increase professional competencies and cultural sensitivity in established and in-training counsellors and mental health professionals who intend to, or who may currently, work with VC individuals and couples.